Prevalence of Dry Eye in Uyghur and Han Ethnic Groups in Western China. (4th May 2017) - Gong, Ying-Ying; Zhang, Fan; Zhou, Jin; Li, Jing; Zhang, Guang-Hui; Wang, Jun-Liang; Gu, Zhen-Sheng
ABSTRACT: Purpose : To describe and compare the prevalence and characteristics of dry eye among Han and Uyghur persons living in Kashi, the most inland city of China. Methods : A total of 1015 residents of Kashi participated in this 2013 cross-sectional study. To evaluate clinical characteristics, each subject completed (1) a dry-eye questionnaire detailing symptoms of dry eye, (2) Schirmer's I-test (SIT), (3) tear-film break-up time (BUT) test, and fluorescein staining of the cornea. Dry eye was defined as the existence of dry eye symptoms and at least two positive clinical signs. Data were analyzed using SPSS software. The prevalence and risk factors of dry eye were evaluated using a multivariate model. Results : Overall, 282 (27.8%) of the 1015 participants were diagnosed with dry eye (95% confidence interval (CI): range, 25.5–30.1). The prevalence of dry eye among Han persons (37.9 %) (95% CI: range, 35.8–40.0) was higher than that among Uyghurs (21.8%) (95% CI: 19.6–24.0) ( p < 0.05). The prevalence of dry eye was 25.6% (95% CI: range, 23.3–27.8) among men and 28.7% (95% CI: 26.5–30.9) among women ( p > 0.05). Risk factors for dry eye included ethnicity, age, occupation, arthritis, and dry mouth. Conclusions : Our study revealed a higher prevalence of dry eye among Han than Uyghur persons in Kashi. Dry eye was significantly associated with environment and ethnicity.